SONOGRAPHIC ASSESSMENT OF GALLBLADDER SIZE AND MOTILITY AMONG APPARENTLY NORMAL PREGNANT WOMEN IN ANAMBRA STATE, NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Pregnancy had been associated with a number of physiologic changes which affect many organs and systems, for example, the gastrointestinal system. Gallbladder, an accessory organ of digestion could be predisposed to disorders in pregnancy but he nature and to which extent it could be affected remained unclear.Aim: This study aimed to investigate the gallbladder changes that could occur in pregnancy.Materials and methods: A prospective cross-sectional survey design was used to sonographically study 201 pregnant and 27 non-pregnant women who met the inclusion criteria, both in the fasting and post prandial states. Both descriptive and inferential statistics were used to analyze data.Results: Means of age, BMI, fasting gallbadder volume (FGbV), post prandial gallbladder volume (PGbV), ejection fraction (EjF) were respectively, 29.12 ± 7.52years, 26.00 ± 4.23kg/cm, 26. 10 ± 13.32cm, 13.36 ± 8.59cm and 47.38 ± 17.58%. The means FGbV in pregnant women was 26.12 ± 13.35cm, EjF was 47.41 ± 17.61%. The mean FGbV and EjF in the non– pregnant women was 74.15 ± 28.91cm and 77.58 ± 9.74% respectively. Age showed no statistically significant difference with FGbV and EjF. Statistically significant difference existed between BMI and FGbV but not with EjF. No statistically significant difference existed between FGbV and PGbV. The mean fetal gestational age was 25.81 ± 8.41 weeks, and showed no statistically significant relationship with FGbV or EjF.Conclusion: Fasting gallbladder volume and gallbladder motility among pregnant women in Anambra state were both reduced.
Keywords: Gallbladder; Pregnancy; Sonography; Fasting; gallbladder volume; Ejection fraction